GE_GERICHTE P/1432/2017 vom 27. März 2018 - GE Cour de justice (2018)
ESCROQUERIE ; COAUTEUR(DROIT PÉNAL) ; COMPÉTENCE RATIONE LOCI ; TENTATIVE(DROIT PÉNAL) ; PAR MÉTIER ; BLANCHIMENT D'ARGENT ; FIXATION DE LA PEINE ; CONCOURS D'INFRACTIONS ; EXPULSION(DROIT PÉNAL) ; PLAIGNANT ; DÉFENSE D'OFFICE ; MOYEN DE DROIT | CP.146.al1; CP.22.al1; CP.3.al1; CP.8.al1; CP.8.al2; CP.146.al2; CP.305.letbis; CP.47; CP.66.leta; CPP.433; CPP.135